Livestock household census survey in Odisha, India - Swain, Braja; Teufel, Nils; Rahman, Habibar; Lukuyu, Ben (2024)
These data contain one round cross section, livestock assets survey of 75146 households from Odisha, India collected between 2017 and 2018.